The Risk of Not Knowing—How Information Sharing Affects Parents’ Ability to Maintain and Develop Family Ties After a Child’s Removal from Parental Care - Tina Gerdts-Andresen; Anette Ødegård Eriksen (Social Sciences)
The ability of parents to maintain and develop family ties after a child is placed in public care is a fundamental yet challenging aspect of child welfare. While legal frameworks emphasize the preservation of parent–child relationships, limited research has explored how access to information affects parental involvement over time. This study draws on qualitative semi-structured interviews with 31 parents whose children were placed in public care to explore how parents experience information-sharing structures within child welfare services and how these experiences influence their ability to maintain and develop family ties with their children. A thematic analysis identifies three key themes: (1) lack of information, (2) conflicting and inconsistent information, and (3) bureaucratic barriers and systemic obstacles to information. Findings indicate that restricted and unpredictable access to updates fosters uncertainty, emotional distress, and a weakening sense of parental identity. Moreover, discretionary decision-making and institutional constraints contribute to inconsistencies in communication, further reinforcing parental exclusion. These findings highlight the role of information sharing as more than an administrative function; it is a structuring mechanism that facilitates or hinders ongoing parent–child relationships. The study highlights the importance of establishing clearer and more consistent communication structures to ensure that parents remain informed and can maintain a relationship with their child in public care.